CLASSIFICATION AND SELECTION SYSTEM MOTORS FOR REGULATED ELECTRIC - and and (Municipal economy of cities (Technical science), 2013)
The questions of choice of DC machines in electric high power and smooth with a wide range of speed control. Are ways to improve the technical, economic and operational performance of valve engines with two types of converters.